A Sonographic Study on Estimating of Gestational Age by Placental Thickness - Prashanth G Patil; KM Nataraj; Shaik Hussain Saheb (Asian Journal of Medical Radiological Research, 2020)
Background: Knowledge of gestational age (GA) is important because it affects clinical management in many ways. Ultrasonography has provided a safe and noninvasive means of dating a pregnancy. The purpose of the present study is to assess the relationship of placental thickness with gestational age and to compare it with other sonographic parameters used to estimate gestational age. Subjects and Methods: The study included 242 normal pregnant women who knew their last menstrual period (LMP). After taking consent, all the women underwent an ultrasound examination. During the scan, besides measuring routine biometric parameters, Placental thickness at the cord insertion was also measured. A retrospective study was designated to test the hypothesis that placental thickness in an age dependant variable and hence can predict gestational age. In the end, the predicted gestational age by placental thickness was compared with gestational age as determined by other sonographic parameters. Results: Placental thickness showed a linear progression in relation to the menstrual age. The correlation coefficient was found to be 0.86(p<0.001). The regression equation was formulated by regressing gestational age on the measured placental thickness. The correlation coefficient between GA-LMP and GA-USG was 0.92 as compared to 0.86 between GA-LMP and GA-PT. The standard error for other USG parameters was +2.32 compared to +2.96 for placental thickness. Conclusion: Placental thickness being a fusion of menstrual age, can be used to predict the gestational age by using the regression formula. Gestational age calculated by other USG parameters is closer to menstrual age as compared to that by placental thickness. The prediction interval was slightly more when the placental thickness was used instead of other USG parameters. Placental thickness is a good alternative parameter for predicting gestational age in the second and third trimester.